2017
DOI: 10.1021/acs.est.7b02210
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Dietary Sources of Short- and Medium-Chain Chlorinated Paraffins in Marine Mammals through a Subtropical Marine Food Web

Abstract: Our previous study revealed an elevated accumulation of short-chain chlorinated paraffins (SCCPs) and medium-chain chlorinated paraffins (MCCPs) in marine mammals from Hong Kong waters in the South China Sea. To examine the bioaccumulation potential and biomagnification in these apex predators, we sampled the dietary items of marine mammals and tracked the sources of SCCPs and MCCPs through a marine food web in this region. Sixteen fish species, seven crustacean species, and four mollusk species were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
85
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 48 publications
12
85
7
Order By: Relevance
“…Field-derived BMFs for MCCPs were reported by Houde et al11 and Zeng et al56 BMFs reported by Houde et al11 were generally below one. Field-derived BMFs reported by Zeng et al56 were above one but questionable (TableS9, SI).TMF No bioaccumulation of MCCPs was found in the food webs studied by Houde et al11 , NIVA57,58,59 and Huang et al60 Miljodirektoratet 61 and Zeng et al56 otherwise, calculated trophic magnification factors above one, which would indicate an increase in the chemical concentration in the biota with increasing trophical level. However, the TMFs in both studies were derived from concentrations in different tissues and are therefore questionable.…”
mentioning
confidence: 75%
“…Field-derived BMFs for MCCPs were reported by Houde et al11 and Zeng et al56 BMFs reported by Houde et al11 were generally below one. Field-derived BMFs reported by Zeng et al56 were above one but questionable (TableS9, SI).TMF No bioaccumulation of MCCPs was found in the food webs studied by Houde et al11 , NIVA57,58,59 and Huang et al60 Miljodirektoratet 61 and Zeng et al56 otherwise, calculated trophic magnification factors above one, which would indicate an increase in the chemical concentration in the biota with increasing trophical level. However, the TMFs in both studies were derived from concentrations in different tissues and are therefore questionable.…”
mentioning
confidence: 75%
“…SCCP concentration in fish samples from Zhubi Reef and Yongshu Reef ranged from 37.9 to 20.200 ng/g lipid weight (lw) and 75.7-25.400 ng g −1 lw, with ∑SCCP concentration of 3700 ± 6000 ng g −1 lw and 5200 ± 7340 ng g −1 lw, respectively. Different studies have shown that the lipid content is a crucial factor affecting SCCP bioaccumulation in marine environment (Yuan et al 2012;Ma et al 2014b;Zeng et al 2017a). In contrast, the obtained results were different from those of Pearl River Estuary, where lipid level was not the predominant influencing factor for SCCP concentration in marine organism (Huang et al 2019).…”
Section: Sedimentmentioning
confidence: 79%
“…According to Houde et al (2008), SCCPs released during production and use have entered water bodies and have been transferred to sediment and aquatic organisms resulting in bioaccumulation through the food chain. Globally, bioaccumulation and trophic magnification of SCCPs have been studied (Houde et al 2008;Li et al 2017a;Ma et al 2014b;Sun et al 2017;Zeng et al 2017a). In the aquatic environment, SCCPs are more likely to be adsorbed in sediment since they have low water solubility and high carbon partition coefficients (Environment Canada 2008).…”
Section: Aquatic Environmentmentioning
confidence: 99%
“…Higher δ 15 N values in Greenland cod could explain the higher concentrations of these particular SCCPs compared to most other species. Although a previous study in lake trout from the Great Lakes also did not find any correlations between SCCP levels and fish length, weight, age, lipid content, or trophic level (Saborido Basconcillo et al, 2015), recent studies found biomagnification of SCCPs in fish in Liaodong Bay, in a marine food web in the South China Sea, and from oysters to crabs in the Pearl River estuary in China (Huang et al, 2017, 2019; Zeng et al, 2017), as well as biomagnification potential in a food web of the Baltic Sea (de Wit et al, 2020).…”
Section: Resultsmentioning
confidence: 96%